2011
DOI: 10.1002/ca.21216
|View full text |Cite
|
Sign up to set email alerts
|

Clinical anatomy of the coccyx: A systematic review

Abstract: The coccyx has been relatively neglected in anatomical research which is surprising given the population prevalence of coccydynia and our inadequate understanding of its etiology. This systematic review analyzes available information on the clinical anatomy of the coccyx. A literature search using five electronic databases and standard anatomy reference texts was conducted yielding 61 primary and 7 secondary English-language sources. This was supplemented by a manual search of selected historical foreign langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
70
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 54 publications
(77 reference statements)
0
70
0
4
Order By: Relevance
“…The coccyx (from the Greek word ''Kójjtn'' due to its resemblance to the curved beak of the cuckoo) comprises the terminal vertebral segments of the human spine [1]. When subject to pathology it can be a source of debilitating localized pain [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coccyx (from the Greek word ''Kójjtn'' due to its resemblance to the curved beak of the cuckoo) comprises the terminal vertebral segments of the human spine [1]. When subject to pathology it can be a source of debilitating localized pain [2].…”
Section: Introductionmentioning
confidence: 99%
“…There is a remarkable paucity of data on the normal in vivo morphology and morphometry of the human adult coccyx. Most observations on the length and shape of the coccyx have been derived from studies of disarticulated skeletal material [1]. One study using plain radiography in asymptomatic adults [3] and another using computed tomography (CT) in patients with vascular or suspected bowel disease [4] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Anatomical studies showed variations in the localization of this ganglion between the sacro-coccygeal joint and coccyx end. It is mostly located in front of the sacro-coccygeal joint and coccygeal vertebra.…”
Section: Introductionmentioning
confidence: 99%
“…This bone is an important structure in the pelvis the serves as an attachment for ligamentous (sacrospinous, anterior, posterior coccygeal, and lateral sacrococcygeal ligaments) and muscular structures (external anal sphincter, levator ani, and coccygeus muscles). These components prevent the sagging of pelvic contents and are responsible for bowel continence [3] .…”
Section: Introductionmentioning
confidence: 99%